Surgical Outcomes Following Vestibular Schwannoma Resection in Patients over the Age of Sixty-five - Strickland, Ben A.; Rennert, Rob; Zada, Gabriel; Shahrestani, Shane; Russin, Jonathan J.; Friedman, Rick A.; Giannotta, Steven L. (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Vestibular schwannoma (VS) are benign, often slow growing neoplasms. Some institutions opt for radiosurgery in symptomatic patients of advanced age versus surgical resection. The aim of the study is to analyze surgical outcomes of VS in patients over the age of 65 who were either not candidates for or refused radiosurgery.Methods This includes retrospective analysis of VS patients between 1988 and 2020. Demographics, tumor characteristics, surgical records, and clinical outcomes were recorded. Patient preference for surgery over radiosurgery was recorded in the event that patients were offered both. Facial nerve outcomes were quantified using House-Brackmann (HB) scores. Tumor growth was defined by increase in size of >2 mm.Results In total, 64 patients were included of average age 72.4 years (65–84 years). Average maximum tumor diameter was 29 mm (13–55 mm). Forty-five patients were offered surgery or GKRS, and chose surgery commonly due to radiation aversion (48.4%). Gross total resection was achieved in 39.1% (n = 25), near total 32.8% (n = 21), and subtotal 28.1% (n = 18). Average hospitalization was 5 days [2–17] with 75% (n = 48) discharged home. Postoperative HB scores were good (HB1–2) in 43.8%, moderate (HB3–4) in 32.8%, and poor (HB5–6) in 23.4%. HB scores improved to good in 51.6%, moderate in 31.3%, and remained poor in 17.1%, marking a rate of facial nerve improvement of 10.9%. Tumor control was achieved in 95.3% of cases at an average follow-up time of 37.8 months.Conclusion VS resection can be safely performed in patients over the age of 65. Advanced age should not preclude a symptomatic VS patient from being considered for surgical resection.
Keywords: vestibular schwannoma; advanced age; microsurgery; radiosurgery